Evaluating the labor-market effects of compulsory military service - Thomas K. Bauer; Stefan Bender; Alfredo R. Paloyo; Christoph M. Schmidt (Institute for the Study of Labor (IZA), 2009)
We identify the causal effect of compulsory military service on conscripts' subsequent labor-market outcomes by exploiting the regression-discontinuity design of the military draft in Germany during the 1950s. Unbiased estimates of the effect of military service on lifetime earnings, wages, and employment are obtained by comparing men born before July 1, 1937 (the White Cohort) who were exempted from compulsory military service to men who were born on or shortly after this threshold date and hence faced a positive probability of being drafted. We find that the putative earnings advantage and wage premium of those who served in the armed forces vanish when selection effects are taken into account.
Keywords: J31; 330; Causal effect; quasi-experimental estimators; conscription; Wehrdienst; Arbeitskräfte; Lebenseinkommen; Lohn; Erwerbstätigkeit; Deutschland